2020
DOI: 10.1111/cobi.13532
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous guardians as an emerging approach to indigenous environmental governance

Abstract: Over the past 3 decades, indigenous guardian programs (also known as indigenous rangers or watchmen) have emerged as an institution for indigenous governments to engage in collaborative environmental governance. Using a systematic review of peer-reviewed literature for research conducted in Australia, Canada, Aotearoa-New Zealand, and the United States, we sought to characterize the emergence of indigenous guardians in the literature and explore whether guardian approaches are representative of Indigenous appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 59 publications
(148 reference statements)
0
46
0
1
Order By: Relevance
“…Incentivizing citizens to fill in knowledge gaps and embracing community collected data may provide policymakers with the opportunity to mobilize public involvement in making better ecosystem protection decisions. In some Indigenous communities, the concept of Indigenous Guardians has become popular with benefits for the environment (especially for monitoring to inform decisions) and self-determination (Reed et al, 2021). With a continued emphasis on the importance of long-term monitoring from both scientific and citizen or community groups, further discoveries can be made regardless of obstacles such as COVID-19.…”
Section: Support Collaborative Monitoring By Both Scientists and Communities To Allow For Better Decisions In The Face Of Unexpected Evenmentioning
confidence: 99%
“…Incentivizing citizens to fill in knowledge gaps and embracing community collected data may provide policymakers with the opportunity to mobilize public involvement in making better ecosystem protection decisions. In some Indigenous communities, the concept of Indigenous Guardians has become popular with benefits for the environment (especially for monitoring to inform decisions) and self-determination (Reed et al, 2021). With a continued emphasis on the importance of long-term monitoring from both scientific and citizen or community groups, further discoveries can be made regardless of obstacles such as COVID-19.…”
Section: Support Collaborative Monitoring By Both Scientists and Communities To Allow For Better Decisions In The Face Of Unexpected Evenmentioning
confidence: 99%
“…Scientists designed these systems and analyze the data, but the local stakeholders collect the data, make decisions on the basis of the findings, and carry out the management interventions emanating from the monitoring system. These programs include, for example, many Indigenous guardian programs (also known as indigenous rangers or watchmen or -women; Reed et al 2020a ), BirdLife International's monitoring of important bird areas, and fisher and hunter records programs such as wildlife triangle monitoring (Cretois et al 2020 ).…”
Section: What Is Locally Based Monitoring?mentioning
confidence: 99%
“…Even when recognition of IK, values, and worldviews occurs, problems still arise (#19, #22, #23) when translating the rhetoric of reconciliation (particularly prominent in Australia and South African contexts) and inclusion into on-the-ground actions that offer tangible benefits for Indigenous communities [210][211][212][213]. Reed et al (2020) observed that in Australia and elsewhere, Indigenous environmental governance and management regimes are frequently tied up with colonial entanglements whereby Indigenous participants are required to resist and contribute to the expansion of colonial government bureaucracies [214,215]. These types of systems [213,216], which employ state-based recognition of Indigenous rights, knowledge, and values through mechanisms, including co-governance arrangements, can serve as tools that maintain the systems of oppression of Indigenous peoples instead of providing greater opportunities for Indigenous authority, self-determination, and sovereignty over their ancestral lands, waters, and seas.…”
Section: Recognitional Injusticementioning
confidence: 99%